Changes in health behaviours and health status of novice nurses during the first 2 years of work. (11th February 2019) - Han, Kihye; Kim, Yeon‐Hee; Lee, Hye Young; Cho, Hyeonmi; Jung, Young Sun
Abstract: Aims: To explore changes in health behaviours and health status of novice nurses during the first 2 years of work. Background: Novice nurses experience many difficulties in maintaining healthy behaviours while adapting to clinical settings. However, studies about the health of novice nurses have not focused on changes over time. Design: Longitudinal descriptive study with self‐reported questionnaires. Methods: Data were collected from 493 novice nurses who started work between September 2014 ‐ December 2015 at a tertiary hospital in Seoul. Dietary behaviours, sleep, depressive symptoms, perceived stress and health status were measured at six time points during the first 2 years of work (the first day of orientation before ward placement, 6 weeks after starting work and 6, 12, 18 and 24 months of work). Changes were examined using means or percentages and 95% confidence intervals. Results: Unhealthy dietary behaviours increased across 6 months, continuing for 2 years. Sleep quality and quantity, depressive symptoms, perceived stress and health status first worsened and then improved; however, they were worse than at baseline. Conclusion: Organizational support for novice nurses is urgently needed. Workplace health education programmes will help them adjust to rotating shift work and maintain better health status. Abstract : 目的: 探讨新护士在头两年工作中健康行为和健康状况的变化。 背景: 新护士在适应临床环境的同时, 也在保持健康行为方面遇到诸多困难。然而, 关于新护士健康的研究并没有聚焦于随着时间的推移而发生的变化。 设计: 采用自我报告式问卷的纵向描述性研究。 方法: 收集了自2014年9月至2015年12月在首尔一家三级医院开始工作的493名新护士的数据。在头两年工作中(病房实习前的第一天训练、开始工作后的第六周以及工作的第6、12、18和24个月)六个时间点测量了饮食行为、睡眠、抑郁症状、知觉压力和健康状况。采用了平均值或百分比和95%置信区间来检查变化。 结果: 不健康的饮食行为在6个月内有所增加, 并持续了2年。睡眠质量和睡眠量、抑郁症状、知觉压力和健康状况先是恶化, 而后有所改善;然而, 它们比基线状态时还要差。 结论: 新护士急需组织层次的支持。工作场所健康教育计划将帮助他们适应轮班工作制并保持更佳健康状况。